Value chain, productivity and trade performance in the dairy industry - Gladys Kemitare; Frank Kabuye; Anthony Moni Olyanga; Nichodemus Rudaheranwa (Modern Supply Chain Research and Applications, 2021)
Purpose: The purpose of this paper was to establish the contribution of value chain and productivity to trade performance in the dairy industry using evidence from Uganda. Design/methodology/approach: This study research design is cross-sectional and correlational. Data were collected through a questionnaire survey of 108 dairy farmers, processors and exporters. Data were analysed through correlation coefficients and linear regression using Statistical Package for Social Sciences. Findings: Hierarchical regression results indicate that value chain and productivity contribute significantly to variances in trade performance of dairy products. Therefore, appropriate value chain processes and high levels of productivity lead to increased trade performance in the dairy industry. Research limitations/implications: This study focusses on trade performance of dairy products in Uganda. These research findings are useful for informing the deliberations of academicians, regulators and the business community. The results are applicable to all countries that carry out trade specifically in dairy products. Practical implications: The results are important for trade policy development in the dairy industry. For example, this study informs farmers, processors and exporters of dairy products how value chain activities in dairy farming can be re-aligned to achieve better quality and productivity for exportation. Similarly, the current study provides policy guidance for the relevant ministries such as ministry of trade and other players to come up with holistic policy actions aimed at improving the trade performance of dairy products in the country. Originality/value: To the researchers' knowledge, this is the first study that provides an initial empirical evidence on the contribution of value chain and productivity on trade performance of dairy products in Uganda.
Keywords: 650; Trade performance; Value chain; Productivity; Dairy products; Uganda